The Cardiac Rehabilitation Inventory: A New Method of Tailoring Patient Support. Issue 2 (March 2016) - Micklewright, Dominic; Northeast, Laura; Parker, Penny; Jermy, Michelle; Hardcastle, Jane; Davison, Ruth; Sandercock, Gavin; Shearman, Jeremy
Abstract : Background: Uptake and adherence to cardiac rehabilitation (CR) are low, and a contributing factor to this may be the practical difficulties of providing a tailored CR environment suited to individual preferences and needs. Objective: The aim of this study was to develop and test a short questionnaire that CR practitioners can use to understand individual patient need and tailor support accordingly. Methods: A conceptual framework of engagement in CR was derived from a comprehensive literature review and the content analysis of semistructured interviews with 15 CR patients. The conceptual framework was used to construct the first version of the Cardiac Rehabilitation Inventory (CRI), which comprised 42 items. Responses on the CRI were measured using a 5-point Likert scale. The CRI was administered to 380 phase III and IV CR patients, and factor analysis (FA) was used to identify salient CR engagement factors. Results: The simplest structure found using FA was three 6-item subscales that all had good levels of internal consistency (Cronbach's α ) and were labeled (a) outcome anxiety, α = .726; (2) process anxiety, α = .724; and (3) autonomy, α = .653. The 3-factor CRI model was verified using confirmatory FA (CMin/ df = 3.2, root-mean-square error of approximation = 0.073). Attenders were found to have higher levels of outcome anxiety than nonattenders ( P < .001), and precontemplator nonattenders were found to have lower autonomy compared with attenders ( P < .001). Standard multiple regression analysis indicated outcome anxiety was a strong predictor of CR intentions ( r 2 = 0.716), followed by autonomy ( r 2 = 0.110) and process anxiety ( r 2 = 0.031). Conclusions: The CRI is a reliable method of measuring CR outcome anxiety, process anxiety, and autonomy. These CRI measurements provide rehabilitation practitioners with valuable information that can help provide individual tailored support.